P653 Modeling the impact of partially efficacious gonorrhea vaccines. (14th July 2019) - Seedat, Shaheen; Abu-Raddad, Laith
Abstract : Background: Gonorrhea is one of the most common sexually transmitted infections. Current control measures are inadequate and are threatened by the emergence of gonococcal antimicrobial resistance. This emerging challenge calls for a vaccine which will reduce the circulation and transmission of this infection, and thus emergence of drug-resistant strains in the population. Methods: A novel deterministic compartmental mathematical model of the heterosexual transmission of Neisseria gonorrheae was constructed to assess the impact of a pre-exposure (prophylactic) vaccine. Results: Catch-up vaccination with a prophylactic vaccine introduced in 2020, with vaccine efficacy in reducing susceptibility of 50% and vaccine coverage of 80% at 2030, reduced gonorrhea prevalence by 29% by 2030, 34% by 2040, and 37% by 2050. The number of vaccinations needed to avert one infection was 31 in 2030, 24 in 2040, and 13 in 2050. Through age group prioritization, the number of vaccinations needed to avert one infection (in 2030) ranged from 24 for the 15–19 years age group, to 50 for the 45–49 age group. Through risk group prioritization (also in 2030), prioritizing the highest sexual risk group (such as female sex workers) was most effective with only 1 vaccination needed per infection averted. Meanwhile, for the lowest sexual risk group (general population), 110 vaccinations were needed per infection averted. Conclusion: Even a partially efficacious gonorrhea vaccine can considerably reduce the prevalence of infection. Vaccine effectiveness is optimized by targeting high sexual risk groups and young individuals. Disclosure: No significant relationships.